Systems resource allocation algorithm for RIS-assisted D2D secure communication based on parallel CNN - Zhengyu ZHU; Gengwang HOU; Chongwen HUANG; Gangcan SUN; Wanming HAO; Jing LIANG (Tongxin xuebao)
To meet the requirements of intelligent signal processing and physical layer security, aiming at the shortage of spectrum resources, a resource allocation algorithm for reconfigurable intelligent surface (RIS)-assisted the device to device (D2D) communication was proposed.D2D users communicated by multiplexing the spectrum resources of cellular users.Considering the constraints of D2D transmission rate, base station transmission power and RIS transmission phase shift, the problem of maximizing user security rate was formulated.To solve the nonlinear programming problem, a parallel convolutional neural network (CNN) algorithm was proposed to obtain the optimal resource allocation scheme.Simulation results show that the parallel CNN algorithm can effectively improve the secrecy rate and it is significantly better than other benchmark algorithms.